The Temple of the Ruby of Fire - Scholastic Inc. (New York : Scholastic, 2004)
Mouse journalist Geronimo Stilton sets out on a quest to find the Ruby of Fire, a gem hidden in the depths of the Amazon jungle.
Translation of: Il tempio del rubino di fuoco.
"Geronimo Stilton."
3.6
3-6
3-6
Keywords: Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Rubies -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Fiction; Mice -- Fiction; Gems -- Fiction; Adventure and adventurers -- Fiction; Stilton, Geronimo (Fictional character) -- Fiction; Mice -- Fiction; Gems -- Fiction; Adventure fiction; Adventure fiction